Anomalie ed estremismi nella lingua delle rime di Sannazaro (Quaderni di Gargnano, 2020)
The paper investigates some aspects of the princeps of Sannazaro's lyrics, published posthumously in Naples in 1530 by Sultzbach. In particular it evaluates the long Errata corrige: in the correction of many errors the linguistic deviations of the printing from the text left by Sannazaro are implicitly manifested. Also the substitutions that two immediately successive editions (Rome, Blado 1530 and Venice, Zoppino 1532) make on the princeps help to circumscribe the specific character of Sannazaro's linguistic choices in vernacular poetry. L’articolo indaga su alcuni aspetti della princeps delle rime di Sannazaro, apparsa postuma a Napoli nel 1530 per i tipi di Sultzbach. In particolare si valuta il lungo Errata corrige conclusivo: nella correzione di molti errori si manifestano implicitamente gli scarti linguistici della stampa dal testo lasciato da Sannazaro. Anche le sostituzioni che due edizioni immediatamente successive (Roma, Blado 1530 e Venezia, Zoppino 1532) operano sulla princeps aiutano a circoscrivere la specificità delle scelte linguistiche del Sannazaro volgare.
Keywords: Sannazaro; Sonetti et canzoni; lingua; Errata corrige; princeps; Sultzbach